An Exploratory Study of Video Game Pricing in the Southeast Asian Market - Wibowo, Tony; Sandriawan, Elfan; Eryc (ULTIMA InfoSys, 2025)
This exploratory study examines optimal video game pricing within the Southeast Asian market from the perspective of gamers. Employing a two-phase quantitative analysis of 405 respondents across six nations—Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam—the study identifies a consistent psychological pricing framework. Key findings reveal two stable price thresholds: a normative expectation of approximately USD 20 for indie titles and an upper limit of USD 40–60 for premium AAA games. The research confirms a significant market transition from price sensitivity to value sensitivity, where developer reputation and production quality directly influence price acceptance. Furthermore, the study substantiates the emergence of a "premium indie" category, indicating consumers are willing to invest more in independent games that demonstrate high levels of trust, quality, and artistry. These insights offer crucial guidance for developers and publishers, highlighting the need for localized pricing strategies that respect established value perceptions while adjusting for regional purchasing power. This study addresses a notable gap in the literature concerning consumer pricing behavior in the rapidly growing Southeast Asian gaming market.